Hodnocení finanční výkonnosti podniku prostřednictvím benchmarkingu - Jelínek, Marek (Vysoké učení technické v Brně. Fakulta podnikatelská, 2024)
Náplní této diplomové práce bude měření a následné hodnocení finanční výkonnosti vybraného podniku prostřednictvím benchmarkingu. Celková práce bude rozdělena na část teoretickou, praktickou a poslední část návrhovou. Teoretická část této závěrečné bude popisovat relevantní pojmy, postupy a aplikace benchmarkingu. V další, analytické části bude analyzovaný podnik podroben analýze a měření dle dříve popsaných metod. V poslední závěrečné části budou předloženy konkrétní návrhy ke zlepšení finanční výkonnosti podniku a zároveň minimalizování zjištěných problémů.

The content of this thesis will be the measurement and subsequent evaluation of the financial performance of a selected company through benchmarking. The overall work will be divided into theoretical, practical, and the final proposal sections. The theoretical part of this conclusion will describe relevant concepts and the application procedures of benchmarking. In the subsequent analytical section, the company will undergo analysis and measurement using the methods described earlier. In the final concluding section, specific proposals for improving the financial performance of the company will be presented, along with minimizing the identified problems.
The Evaluation of the Company's Financial Performance Using the Benchmarking Approach
Keywords: Benchmarking; finanční analýza; finanční výkonnost; poměrové ukazatele; analýza prostředí; výkaz zisku a ztráty; rozvaha; Benchmarking; financial analysis; financial performance; ratio indicators; environmental analysis; income statement; balance sheet.